THE MIGRATION ECOLOGY OF FINNISH BLACK-TAILED GODWITS (Limosa limosa) - Timonen, S. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
The description of migration routes and migration strategy of the northernmost Black-tailed Godwit population in Europe, located in Central Finland, is presented. We studied migration with ring resightings (200 encounters) and geologgers (16 individuals). The comparison of the datasets are discussed. This is the first published larger data of migration within the northern and eastern European godwit subpopulations, enabling comparison with the more studied West European subpopulations.
Миграционная экология финских больших веретенников (Limosa limosa)
Keywords: Black-tailed Godwit; migration; color-ringing; geologgers